The development and validation of a work-flow scale - Mahajan, Devyani Satchit (Kansas State University, 2020)
The definition of flow has been put forth by Csikszentmihalyi (1975) as “the holistic sensation that people feel when they act with total involvement”. Even though the original definition of flow has been widely accepted, there still exist varied approaches to measure the construct. Despite there being several scales that measure flow, there are still a number of psychometric issues associated with the measurement of flow. This dissertation attempts to address these issues, by first, developing a measure of flow in the workplace, by operationalizing flow based on its original definition. In the first study, items in the scale were developed to measure the dimensions and the preconditions of flow. Based on the results of the first study, models that measured the dimension and the preconditions of flow, separately, showed the best fit. Furthermore, a nomological network was examined in the second study to assess the construct validity of the scale. Results did show convergent and divergent validity flow had with its antecedents and consequences, but the model did not show a good level of fit. Partial and full mediation models, with job satisfaction as a mediator are also examined in the second study. The partial mediation model showed the best fit. Finally, concurrent validity of the scale was also examined, by correlating it with the Work-Related Flow Scale (Bakker, 2008), results of which showed a moderate correlation (r = 0.66), thereby suggesting that there was a difference in the manner in which both scales measured flow. Current research not only provides a theoretically developed short measure of flow, but also, by examining job satisfaction as a mediator, provides insight and evidence into how job satisfaction can influence certain consequences faced by employees.
Keywords: Flow; Measurement of flow; Scale development; Flow at work